Ultrathin graphene oxide-based hollow fiber membranes with brush-like CO2-philic agent for highly efficient CO2 capture - Zhou, Fanglei; Tien, Huynh Ngoc; Xu, Weiwei L.; Chen, Jung-Tsai; Liu, Qiuli; Hicks, Ethan; Fathizadeh, Mahdi; Li, Shiguang; Yu, Miao (Nature communications, 2017)
Among the current CO 2 capture technologies, membrane gas separation has many inherent advantages over other conventional techniques. However, fabricating gas separation membranes with both high CO 2 permeance and high CO 2 /N 2 selectivity, especially under wet conditions, is a challenge. In this study, sub-20-nm thick, layered graphene oxide (GO)-based hollow fiber membranes with grafted, brush-like CO 2 -philic agent alternating between GO layers are prepared by a facile coating process for highly efficient CO 2 /N 2 separation under wet conditions. Piperazine, as an effective CO 2 -philic agent, is introduced as a carrier-brush into the GO nanochannels with chemical bonding. The membrane exhibits excellent separation performance under simulated flue gas conditions with CO 2 permeance of 1,020 GPU and CO 2 /N 2 selectivity as high as 680, demonstrating its potential for CO 2 capture from flue gas. We expect this GO-based membrane structure combined with the facile coating process to facilitate the development of ultrathin GO-based membranes for CO 2 capture. Membrane separation technologies show promise for CO 2 capture, but typically suffer from a trade-off between permeance and selectivity. Here, the authors produce hollow fiber membranes coated with graphene oxide and a CO 2 -philic agent that can efficiently separate CO 2 from flue gas under wet conditions.